Potret Religiusitas Masyarakat Miskin Pemukiman Kumuh Kampung Tambakrejo, Kota Semarang - dan Arqom Kuswanjono, Agustinus Sugeng Priyanto, Irwan Abdullah, (Faculty of Social Science, Universitas Negeri Semarang, 2015)
Religious behavior is largely determined by the perpetrator as a person living in a society. Similary, individuals who live in poor communities in slums. Practice religiosity of the poor in the slum of Kampung Tambakrejo, Semarang City is dominated by the traditions or customs of society for generations to grow and thrive in it. The main influence in their religious life into a social identity that is consisten with the concept of